Prevention of facial injuries caused by personal protective equipment during the COVID-19 pandemic - Geraldo Magela Salomé; Rosimar Aparecida Alves Dutra (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Develop and validate a leaflet to guide health professionals in preventive measures related to injuries caused by the use of personal protective equipment during the COVID-19 pandemic. Methods: For the construction of the brochure, an integrative review was carried out in the main databases. The evaluation of the leaflet was made by 59 health professionals (nurses, physiotherapists, and doctors), using the Delphi technique. Results: In the first evaluation cycle, the items in the brochure were considered by the judges to be "inadequate" to "adequate"; the Content Validity Index was 0.80-1.0. After the adjustments suggested by the judges were implemented, the leaflet was sent back to the second evaluation cycle, in which all items were considered "adequate", resulting in a Content Validity Index of 1.0. Conclusion: The developed brochure has content validity and can assist health professionals in preventing injuries caused by the use of personal protective equipment the developed brochure has content validity and can assist health professionals in preventing injuries caused by the use of personal protective equipment.